Efficient Communication Skills and Patient Satisfaction - Shaheen, Zubaida; Ghaffar, Sadia A; Kanwal, Rehana; Mumtaz, Faria; Nosheen, Javeria; Khan, Junaid Sarfaraz (Journal of Rawalpindi Medical College, 2025)
Objectives: To compare the patient satisfaction levels before and after conducting a short course of one month on communication skills. Methods and Materials: A Quasi-experimental study was conducted at CMH Chunian from January till June 2023.Two hundred patients admitted to the hospital for at least 48 hours were selected. All patients provided their feedback by filling out a Feedback was taken from 100 patients before the communication skills course. After the communication skills course, all nurses were advised to follow the instructions and guidelines taught during the course. Feedback was taken from 100 patients after the course. Both groups were compared in terms of age, gender, hospital stay and questionnaire score. Results: In group A, duration of admission ranged from 2 to 14 days with a mean and standard deviation of 4.69±2.11 days. In group B, duration of admission ranged from 2 to 9 days, with a mean and standard deviation of 4.22±2.13 days (p-value 0.07). Group B patients were more satisfied as compared to the group A patients with scores of 85.31±10.0 and 73.34±9.82 (p-value 0.00). Conclusion: It is concluded in our study that there was a great improvement in the patient satisfaction level after the conduct of the short-duration course on communication skills for nurses of our institute.